Situation Report: Yugoslavia, 14 November 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Communist System Blamed for Crisis / by Slobodan Stankovic Central Committee Admits Major Failures / by Slobodan Stankovic Relations with Bulgaria: Political Difficulties; Economic Progress / by Slobodan Stankovic New Soviet Party Program Welcomed / by Slobodan Stankovic Further Volume of Memoirs by Former Yugoslav Ambassador to the USSR / by Slobodan Stankovic New Book on the Weak Spots of Socialism